Data Processing and Scientific Articles Writing Training to Improve the Professionalism of Middle School Mathematics Teachers in the Northern Region of Solok Regency, West Sumatera - Sari, Shinta; Murni, Dewi; Helma, Helma; Mirna, Mirna (Fakultas MIPA Universitas Negeri Padang, 2024)
Writing scientific articles is crucial for a professional teacher. However, the reality shows that very few teachers are willing, able and accustomed to producing scientific articles. Based on the results of observations and discussions with teachers and heads of the Mathematics Teachers Association of Junior High Schools in the Northern Region of Solok Regency, it was found that teacher is facing two problems including motivation and techniques in scientific writing. Therefore, a solution to this problem is to hold data processing and scientific article writing training. The training was carried out in four stages, namely presentations and discussions, data collection, data processing with Microsoft Excel, and writing the results of data processing into a scientific article and learns how to publish it. The results of the teachers' personal self-evaluation showed that from this training there is an increase in their motivation and ability in processing data and writing scientific articles.